Human Resource Management in Professional Services Firms: Too Good to Be True? Transcending Conflicting Institutional Logics. (May 2015) - Bévort, Frans; Poulfelt, Flemming
Why is it that HR specialists appear to have difficulty applying their knowledge, systems and techniques in a systematic way when it comes to professional services firms (PSFs) – particularly when the drivers for developing powerful HRM practices within such businesses seem more pressing than ever? This paper analyzes the ways HR specialists and PSF managers/partners differ in their understanding of organizations and their management. The analysis supports the argument that, while HR specialists and the discipline of HRM are governed by bureaucratic logic in their approach to management, PSF managers by contrast are driven by professional logic. This creates a number of subtle as well as explicit tensions and disconnects that will have to be tackled if the practices of HRM are to prevail in PSFs. This paper contributes to HRM literature as well as institutional theory, by applying an analysis of institutional logics to HRM practice in PSFs. The paper builds on interviews with five HR managers who have held positions in PSFs, as well as a longitudinal case study of PSF managers in one of the 'Big Four' accounting firms. The paper offers a number of tentative proposals around how HRM and PSFs might transcend the described gulf between the two approaches to management.